Noonan syndrome‐like disorder with loose anagen hair: A second case with neuroblastoma. (5th April 2015) - Garavelli, Livia; Cordeddu, Viviana; Errico, Stefania; Bertolini, Patrizia; Street, Maria Elisabeth; Rosato, Simonetta; Pollazzon, Marzia; Wischmeijer, Anita; Ivanovski, Ivan; Daniele, Paola; Bacchini, Ermanno; Lombardi, Alfonsa Anna; et al.
<x xml:space="preserve">Abstract</x> Noonan‐like syndrome with loose anagen hair (NSLH), also known as Mazzanti syndrome, is a RASopathy characterized by craniofacial features resembling Noonan syndrome, cardiac defects, cognitive deficits and behavioral issues, reduced growth generally associated with GH deficit, darkly pigmented skin, and an unique combination of ectodermal anomalies. Virtually all cases of NSLH are caused by an invariant and functionally unique mutation in SHOC2 (c.4A>G, p.Ser2Gly). Here, we report on a child with molecularly confirmed NSLH who developed a neuroblastoma, first suspected at the age 3 months by abdominal ultrasound examination. Based on this finding, scanning of the SHOC2 coding sequence encompassing the c.4A>G change was performed on selected pediatric cohorts of malignancies documented to occur in RASopathies (i.e., neuroblastoma, brain tumors, rhabdomyosarcoma, acute lymphoblastic, and myeloid leukemia), but failed to identify a functionally relevant cancer‐associated variant. While these results do not support a major role of somatic SHOC2 mutations in these pediatric cancers, this second instance of neuroblastoma in NSLAH suggests a possible predisposition to this malignancy in subjects heterozygous for the c.4A>G SHOC2 mutation. © 2015 Wiley Periodicals, Inc.